Indigestible neutral detergent fiber evaluation with incubation in different species - Bettero, V. P. [UNESP]; Campos, A. F. [UNESP]; Dib, V. [UNESP]; Del Valle, T. A.; Zilio, E. M.C.; Teixeira, I. A.M.A. [UNESP]; Siqueira, G. R. [UNESP]; Rennó, F. P. (Cordoba University Press (UCOPress), 2021)
We aimed to evaluate indigestible neutral detergent fiber (iNDF) feed concentration after cattle, goat, and sheep ruminal incubation, compare results with different estimate methods and connect with chemical analysis data. Four forages (corn silage, sugarcane, Brachiaria decumbens cv. Marandu, and Panicum maximum cv. Tanzânia), two concentrates (ground corn and soybean meal), a by-product (soybean hull), and three fecal samples (cattle, goat, and sheep) were incubated in Nellore steers, dry Saanen goats and Santa Inês sheep. Animals were previously adapted to the experimental diet for eight days, and incubation was performed for 240 hours. The concentration of iNDF was higher when samples were incubated in goat rumen compared with samples incubated in the rumen of cattle. Sheep ruminal incubation increased forages and tended to increase concentrate and by-product iNDF concentration, relative to cattle ruminal incubation. Moreover, sheep and goat ruminal incubation result in similar feed iNDF concentration. Besides, cattle feces had a higher level, and goat feces had lower iNDF levels than sheep feces. The CNCPS underestimated iNDF feed concentration. Estimates of uNDF from Conrad et al. (1984) were lower than iNDF level of sugarcane and higher than iNDF level of P. maximum and concentrates. In general, lignin concentration was the primary composition data related to the iNDF level. However, ADF was the best for forages (R2 = 0.668), and NDF was better for concentrates (R2 = 0.454). In conclusion, digestive process of different species affects iNDF feed concentration. The bias of models was considerable, and feed characteristics affect chemical composition and iNDF level.
Evaluación de fibra detergente neutra indigestible con incubación en diferentes especies
Keywords: Additional Digestibility; NDF; Polygastric; Rumen